2006
DOI: 10.5005/jcdp-7-1-117
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Myxoma – A Case Report and Clinico-Radiographic Study of Seven Tumors

Abstract: The primary aim of this paper is to present clinical and radiographic aspects of odontogenic myxomas diagnosed at the Stomatology Clinic of Bauru School of Dentistry, University of São Paulo, Brazil and to compare them with data reported in a series published in the literature. A second objective is to report a clinical case of odontogenic myxoma in a 9-year-old patient in whom the lesion involved the anterior region of the maxilla. Dental records between 1975 and 2000 were reviewed and seven cases diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
2
6
0
8
Order By: Relevance
“…In this case, the tumor was located in the left posterior maxilla region, invading the maxillary sinus. As far as the x-ray is concerned, most authors report a multilocular radiolucent image as the most commonly found -as it happened in our case, and in this image we did not see bone perforation and maxillary sinus invasion, which was proven by the CT scan, thus proving its importance for the treatment of the lesion 6 . The treatment performed was tumor resection with healthy tissue margins, which is the one most advocated by the authors, especially in the maxilla and the posterior region, because of the very difficulty in clinically establishing tumor invasion level and complete lesion removal by means of a more conservative technique4.…”
Section: Discussionsupporting
confidence: 68%
“…In this case, the tumor was located in the left posterior maxilla region, invading the maxillary sinus. As far as the x-ray is concerned, most authors report a multilocular radiolucent image as the most commonly found -as it happened in our case, and in this image we did not see bone perforation and maxillary sinus invasion, which was proven by the CT scan, thus proving its importance for the treatment of the lesion 6 . The treatment performed was tumor resection with healthy tissue margins, which is the one most advocated by the authors, especially in the maxilla and the posterior region, because of the very difficulty in clinically establishing tumor invasion level and complete lesion removal by means of a more conservative technique4.…”
Section: Discussionsupporting
confidence: 68%
“…The typical soft, slippery and gelatinous nature of the specimen on macroscopic examination[613] and the histopathological findings were also in accordance with the literature. [25611] Thus our case was a prototype of an odontogenic myxoma.…”
Section: Discussionmentioning
confidence: 83%
“…[6] Secondly, it is derived from the mesenchymal portion of the tooth germ i.e., the dental papilla, follicle or periodontal ligament (PDL). [1117]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces tumeurs dont la pathogénie est encore controversée représentent 0,04 à 0,6 % des tumeurs de la cavité buccale et 3 à 7% des tumeurs odontogéniques [1,2,3]. Les séries rapportées dans la littérature portent sur des cas isolés [1,2,4,5,6,7,8,9,10,11]. Bien que bénignes, ces tumeurs sont localement agressives imposant une prise en charge appropriée.…”
Section: Introductionunclassified